Effectiveness of Cognitive-Behavior Training on Modifying Self and Other- Deception among Females with Irrational Beliefs - Agahheris, Mojgan; Ezzati, Katayoon; Dousti, Akram; Pallooji, Abbas (International Journal of Applied Behavioral Sciences, 2019)
Introduction: Self-deception and other-deception can be understood as lying to themselves and others. This research aimed to evaluate the efficacy of cognitive-behavioral intervention on improving self-deception and other-deception in women with irrational beliefs. Methods: This quasi-experimental study was conducted with two groups of experimental and control and by implementation of pre- and post-test, and using sample of 30 participants (15 in experimental group and 15 in control group). The sampling method was convenient method among volunteer women eligible to inclusion-exclusion criteria of research object. Measuring tools were Self-deception and other-deception and irrational beliefs questionnaires. Data were analyzed using MANOVA test. Results: Cognitive-behavioral intervention reduced self-deception, other-deception, and irrational beliefs in the experimental group compared with the control group (P<0.05). Conclusion: According to this results study, cognitive-behavioral therapy can be an efficient intervention for the correction of irrational beliefs, self-deception and other-deception. Declaration of Interest: None Key words: Cognitive-behavioral intervention, Irrational beliefs, Self-deception, Other-deception.